The effectiveness of The Use of The Form of Jigsaw in The Reading Skill of The Islamic Middle School Shining Sedan Rambang - Agustina, Nur Thoyibatin (Universitas Muhammadiyah Sumatera Barat, 2021)
Reading skill is one of the important points of the four skills that often students have difficulty in Arabic learning. Among the factors that support the achievement of goals are methods, medias, learning model, strategies, curriculums, and students' backgrounds. In this study, the researchers used cooperative learning of Jigsaw model. Jigsaw model is the students’ way to share knowledge and experience with other groups. The aimed is making fast and easy of the learning process to be understood. The objectives of this study were 1) Knowing how the Jigsaw model of cooperative learning process in learning reading skill (maharah qiro'ah) at Islamic Junior High School of As Sathi’ Sedan Rembang. 2) Measuring the extent of the influence of the Jigsaw model in learning reading skill (maharah qiro'ah) in Islamic Junior High School of As Sathi’ Sedan Rembang. The research method was an experimental method with a quantitative approach consisting of two groups. The first group is the non-experimental class (control). The second group is the experimental class. The instruments which used in data collection in this study were documentation, observation and tests in the form of pre-test and post-test. The results of this study shown that: 1) The cooperative learning of Jigsaw model in learning reading skill (maharah qiro'ah) can improve students' reading skill, apply appropriate vocabulary usage, and make the students easy to understand the reading text and also made students are motivated, understood, and enthusiastic in learning reading skill, because the learning process was felt more fun by students. 2) The t-test = 6.78 were greater than the t-table (significant list) 1% = 2.39 and 5% = 1.67. Its means that H1 was accepted.